2021
DOI: 10.1097/mcg.0000000000001478
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and Safety of Statin for Hepatocellular Carcinoma Prevention Among Chronic Liver Disease Patients

Abstract: Introduction and Aim: Hepatocellular carcinoma (HCC) is a deadly complication among patients with chronic liver disease (CLD). Controversies on the efficacy and safety of statin to prevent HCC among patients with CLD remain despite the growing evidences. We aim to investigate the efficacy and safety of using statin for HCC prevention among adult with CLD. Methods: We performed a systematic search of 4 electronic databases (PubMed/MEDLINE, EMBASE, Cochra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(15 citation statements)
references
References 39 publications
(214 reference statements)
2
12
0
Order By: Relevance
“…Consistent with this study, the negative association between statin use and the liver cancer risk has been identified in previous observational studies [ 45 ]. Meanwhile, we observed an elevated risk of liver cancer in metformin users, a finding that conflicts with results of previous studies [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…Consistent with this study, the negative association between statin use and the liver cancer risk has been identified in previous observational studies [ 45 ]. Meanwhile, we observed an elevated risk of liver cancer in metformin users, a finding that conflicts with results of previous studies [ 46 , 47 ].…”
Section: Discussionsupporting
confidence: 92%
“…5,6 Similarly, statin use in retrospective studies was subjected to indication bias and immortal time bias, which was discussed in our prior study. 7 We agree with the author that the presence of T2DM, smoking, and statin use could influence the risk of cardiovascular death (which is a competing event for liver decompensation). While interesting, this is beyond the scope of our current study and should be specifically addressed in future study.…”
Section: To the Editorsupporting
confidence: 70%
“…Several studies have demonstrated that a high-fat, high-cholesterol diet can trigger HCC in mice, 122 , 134 , 140 , 141 via a neoplastic transformation of hepatocytes caused by broad transcriptional deregulation of genes involved in metabolic pathways (`metabolism in cancer´ hallmark) and calcium signalling. 140 It has been shown that statins, which block hepatic cholesterol synthesis, protect against HCC 142 and CCA 143 development, as well as resulting in decreased risk of mortality. 144 On the other hand, a higher serum cholesterol level was shown to be reflective of conserved liver function and decreased mortality.…”
Section: Deregulation Of Lipid Metabolism In Liver Cancermentioning
confidence: 99%